Transfer Of Rights Over The Waste Land Of The Waduk Irrigation Agency Province Of East Java To Pensiants Of State Employees Based On A Letter To The Governor's Decision (Juridical Analysis Of The Decision Of The Bangil District Court Number 17/Pdt.G/2020/Pn.Bil) - Syaichul Ibad, Mochamad (Universitas Islam Malang, 2024)
Abstract : Land is a primary need for the population for both housing and employment. To obtain legal certainty over land rights, it is necessary to have regulations governing the acquisition and transfer of community land rights, including the acquisition and transfer of property rights over community land originating from state land. The purpose of this research is to examine in depth the validity of the process of transferring the land rights of the reservoir assets of the East Java Provincial Irrigation Office to 7 retired Civil Servants (PNS). This research uses a normative juridical research method, which emphasizes the analysis of legal issues by using legal principles, laws and regulations and library materials related to the legal issues studied and analyzed in this research. The result of this research is that the authority of PPAT is authorized to make a Land Deed based on the Decree of the Governor of East Java on the assets of the East Java Provincial Irrigation Service reservoir to 7 Retired Civil Servants (PNS) at the time after being upgraded to a Certificate of Ownership and transferred to a Legal Entity / Developer, and also by existing regulations the transfer of rights to land assets of the former East Java Provincial Irrigation Service reservoir is legal so that it has permanent legal force. (Inkracht van gewijsde)Keywords: Transfer of Rights, PPAT, Reservoir